Modelling Of Sensorless MPPT Controller For Variables Speed PMSG Wind Turbine Stand-Alone System - Tiang, Tow Leong (2012)
This thesis presents an assessment of the wind energy potential at Bayan Lepas in Penang Island, Malaysia and also the modelling of wind energy conversion systems (WECS) by using Matlab/Simulink. An overall modeling system illustrates the simulation of a simplified sensorless maximum power point tracking (MPPT) control strategy for capturing maximum energy from the fluctuating wind-speed in stand-alone small scale variable speed wind turbine generator system (VSWTGS) using permanent magnet synchronous generator (PMSG) and an inverter controller of a deadbeat-based proportional-integral (PI) sinusoidal pulse-width-modulation (SPWM) controller is applied in single-phase voltage source inverter (VSI) for sending power to stand-alone load. The proposed sensorless MPPT controller for a stand-alone small scale direct-driven PMSG WTGS also has been simulated in energy storage system. In addition, an inverter system describes the simulation of a deadbeat-based PI SPWM controller for stand-alone VSI using battery cell as primary energy sources. The wind data were statistically analyzed using Rayleigh distribution function in wind energy potential assessment. The results show that the measurement site falls under Class 1 of the International System Wind Classification. The climate in Penang Island is highly influenced by the Northeast (NE) and Southwest (SW) monsoon seasons. The mean annual wind power density (WPD) and mean annual wind energy density (WED) are estimated to be about 24.54 Wm-2 and 17.98 kWhm-2month-1, respectively. The total annual WED is 216 kWhm-2year-1.